PENERAPAN PERGERAKAN KAMERA DINAMIS PADA FILM PENDEK BUKAN SALAHKU DI CV LUAR KOTAK AUDIO VISUAL - I Putu Kevin Andika Prananda; I Kadek Puriartha; Made Rai Budaya Bumiarta (CALACCITRA: JURNAL FILM DAN TELEVISI, 2023)
The film is a medium that uses moving images and sound to tell a story or convey a message to the audience. Films can be made in various genres, such as drama, comedy, action, horror, and so on, and can be watched in theaters or on platforms that provide streaming services. In addition, films can also be made in various formats, such as feature films or short films. Dynamic camera movement allows the camera to move during shooting to provide a more dynamic and interesting visual effect. This technique can be used for various purposes, such as following the action that is happening, providing a different perspective, or creating a certain atmosphere. Dynamic camera movements can help enhance the visual impression of a film and help create an atmosphere that fits the story being shown. However, too much camera movement or out-of-context can cause confusion or distraction for the viewer, which needs to be considered carefully in filmmaking. It is hoped that the dynamic camera movements applied in the film "Bukan Salahku" will be well received by the audience, both from the medium and also the media presented. So that the work that is presented becomes a good work, so that it can be exhibited to a wide audience later. Students are expected to be able to further develop in the future in thinking creatively and seeing interesting aspects and having artistic aesthetics to make into works in the future. And also self-development for these students in the future.